The Ukrainian Diaspora’s translating activities of the 20th century: directions and achievements. (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article deals with the Ukrainian translating activities having taken place abroad in the 20th century. The issue has not been studied in details yet. The researchers such as I. Dziuba, M. Ilnytskyi, S. Pavlychko, and etc. focused their attention on some of the most presentable figures, including Ihor Kachurovskyi, Ihor Kostetskyi, and representatives of “the New York Group”. Therefore, the goal of the article is to identify and characterize the directions and achievements of the translating activities of the Ukrainian Diaspora of the twentieth century.The article identifies three main directions of the Ukrainian Diaspora’s translation activity. The development of translation in Ukrainian abroad community is the first direction of this activity. This aspect is connected with the history of translation. I argue that such Ukrainian Diasporic artistic associations as “MUR” and “Slovo” actively developed Ukrainian translation studies abroad. The main achievement of the first association is the understanding of translation as a necessary component for the promotion of the Ukrainian language and culture. However, the main achievement of the second association was edition in different languages of the translations of Ukrainian writings. These translations greatly enriched the theory and practice of artistic translation.As Ukrainian Diasporic translators were usually theorists and critics of artistic translation, the second area of translation activity raises the theoretical issues of translation (such as translation of poetry, study of the principles of translating anthologies, genres of translation, etc.). B. Kravtsiv, B. Lepkyi, I. Kostetskyi, I. Kachurovskyi, etc. studied these issues in their researches. The third area covers the actual artistic practices of Ukrainian Diaspora’s translators, whose figures are generalized on the basis of different criteria. In my opinion, the chronology criteria or the criteria of belonging to a translation school / generation can be interesting for researchers of Ukrainian translation history, because both help trace the evolution of Ukrainian translating activities abroad.
Keywords: translators; Ukrainian Diaspora; artistic translation